On MMSE methods for blind identification of OFDM-based SIMO systems - Alayyan, F.; Shubair, R.; Leung, Yee-Hong; Zoubir, A.; Alketbi, O. (2009)
This paper considers the problem of channel identification in OFDM-based SIMO systems. In this contribution, we focus on minimum mean square error (MMSE) algorithm, which exploits the system structure and offers superior estimation performance. Simulation results are provided to illustrate this claim and to assess the performance of the proposed algorithms. © 2009 IEEE.